2016
DOI: 10.1002/jso.24155
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of primary resected retroperitoneal soft tissue sarcoma: Analysis from a single asian tertiary center and external validation of gronchi's nomogram

Abstract: Our study demonstrated tumor grade and surgical margins had significant prognostic influence and the Gronchi's nomogram has an excellent applicability in predicting survival of STS patients. J. Surg. Oncol. 2016;113:355-360. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…In this context, instruments such as nomograms are useful to physicians for prognostication; thus a prognostic nomogram for RPS was included in the last version of the AJCC staging system. Available nomograms specific for RPS are detailed in Table …”
Section: Nomograms For Rpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, instruments such as nomograms are useful to physicians for prognostication; thus a prognostic nomogram for RPS was included in the last version of the AJCC staging system. Available nomograms specific for RPS are detailed in Table …”
Section: Nomograms For Rpsmentioning
confidence: 99%
“… External validations were performed on 135 patients from Institut Gustave Roussy in Villejuif, France (Harrell C‐index of 0.67 for the OS nomogram and 0.68 for the DFS nomogram); 631 patients from a multicentric cohort of the Trans‐Atlantic Retroperitoneal Sarcoma Working Group (Harrell C‐index of 0.73 for the OS nomogram and 0.69 for the DFS nomogram); and 144 patients from Taipei Veterans General Hospital in Taipei, Taiwan (Harrell C‐index, 0.72 for the OS nomogram) …”
Section: Nomograms For Rpsmentioning
confidence: 99%
“…Importantly, these models underwent three independent external validations including: single institutional series from Institut Gustave Roussy, Paris, France, a multicentric series from the Trans‐Atlantic Retroperitoneal Sarcoma Working Group (TARPSWG) and a series from Taipei Veterans General Hospital, Taipei, Taiwan . Both nomograms proved to be well calibrated and to maintain a good discriminative ability when applied to external cohorts (Harrell C index ranging from 0.67 to 0.73) as a proof of their broad applicability.…”
Section: Nomograms For Rps Patientsmentioning
confidence: 99%
“…The histologies of SFT, MPNST, and UPS have been included in prognostic analyses and nomograms for primary, resectable retroperitoneal soft tissue sarcomas. These studies have clearly shown that grade and histology‐specific subtype are two very important predictive covariates for overall and disease‐free survival . A striking example is that a low‐grade SFT has a lower long‐term risk of death than does a well‐differentiated liposarcoma (which by definition is also a low‐grade retroperitoneal sarcoma).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have clearly shown that grade and histology-specific subtype are two very important predictive covariates for overall and disease-free survival. 1,[4][5][6]8,10,11 A striking example is that a low-grade SFT has a lower long-term risk of death than does a well-differentiated liposarcoma…”
Section: Introductionmentioning
confidence: 99%